Parking Quota Monitoring System Internet of Things Based - M. Ali Sahbana Pili; Imam Suharjo (Universitas Mercu Buana Yogyakarta, 2025)
The development of science and technology has now progressed rapidly. Humans try to overcome parking problems by adopting automatic equipment systems, replacing manual systems. One approach applied is to design an information model regarding the number of automatic parking areas around the parking lot entrance. This information system will display information regarding the number of parking slots available in the parking area. This research produces systems and tools that can monitor parking quotas using IR sensors. System users can park their vehicles as long as the parking lot is not full and the user's ID card has been registered with the system. By using RFID, the system allows users to park easily without swiping the card first. The system will automatically increase the parking quota if it detects a vehicle leaving the parking area. Based on the results of tests carried out to enter parking automatically where the parking quota has not been met and the ID card that has been registered can run well with a percentage of 98%. Meanwhile, the automatic parking exit system also runs well with a percentage of 98%. This presentation is influenced by the speed of the sensor in reading the presence of the vehicle.